1972
DOI: 10.1136/gut.13.8.589
|View full text |Cite
|
Sign up to set email alerts
|

Nodular lymphoid hyperplasia with hypogammaglobulinaemia

Abstract: SUMMARY A patient with nodular lymphoid hyperplasia, who manifested defects in cellular immunity, is presented. The clinical course is discussed and a review included of the 23 patients thus far reported with nodular lymphoid hyperplasia and hypogammaglobulinaemia.Acquired idiopathic hypogammaglobulinaemia can be associated with a sprue-like syndrome in about 20% of patients (Gitlin, Gross, and Janeway, 1959). Hermans, Huizenga, Hoffman, Brown, and Markowitz (1966) described the association of hypogammaglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…This is probably an underestimate, as barium follow-through examination may not reveal small nodules. Only two patients had giardiasis (Table 3) which is at variance with the findings of Ajdukiewicz (1972) who, in reviewing the literature, found that 15 of 21 patients with NLH had giardiasis. However, many of these cases were from North America where giardiasis accounts for most of the malabsorption in patients with hypogammaglobulinaemia (Ament et al, 1973).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is probably an underestimate, as barium follow-through examination may not reveal small nodules. Only two patients had giardiasis (Table 3) which is at variance with the findings of Ajdukiewicz (1972) who, in reviewing the literature, found that 15 of 21 patients with NLH had giardiasis. However, many of these cases were from North America where giardiasis accounts for most of the malabsorption in patients with hypogammaglobulinaemia (Ament et al, 1973).…”
Section: Discussionmentioning
confidence: 63%
“…The finding of a fibrous capsule around a nodule from MH is not consistent with either a germinal centre or Peyer's patch anology and was probably a 'chance' finding, as in all the other nodules examined there was no sign of such a capsule. Ajdukiewicz et al (1972) in their review, found no evidence that patients with NLH were identifiable by certain in vitro and in vivo immunological tests. Our attempts, using a wider variety of tests, confirm this view (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…The second case [1], however, did have associated dysgammaglobulinemia. The most common immunoglobulin abnormality in patients with NLH is absent or diminished IgA, but there is usually concomitant decreased IgG and absent or near absent IgM [5]. Solitary IgA deficiency, as in our patient, usually occurs in apparently healthy individuals [6].…”
Section: Discussionmentioning
confidence: 95%
“…Among a large number of patients with immunodeficiency syndromes, 80070 of those with intestinal manifestations had concurrent giardiasis [86]. Extraordinarily high incidences of giardial infections have been reported in many clinical series of immunodeficiency syndromes [86][87][88][89][90][91][92][93][94][95]. Whether reduced intestinal levels of immunoglobulins predispose to giardiasis in individuals without frank immunodeficiency syndromes is a matter of controversy.…”
Section: Synergismmentioning
confidence: 99%